Shared learning and participatory evaluation: The sistematización approach to assess development interventions - Tapella, Esteban (2014)
The sistematización approach is a multi-stakeholder strategy to assess development interventions with emphasis on the lessons learned. Apart from briefly highlighting sistematización roots in Latin America, as well as its similarities with other evaluation streams, the article concentrates mainly on the concept and method of sistematización itself, its scope and limitations. Recognizing that there are several approaches to systematize development interventions, the article introduces a basic ‘method’. In the final section, it is argued that introducing this endogenous approach from Latin America may serve as an additional brick in building the evaluation field in this and other regions of the world.